(untitled) (Research, Society and Development, 2021)
Quinones are a classic example of molecules isolated from natural products. These compounds are secondary metabolites produced by plants, fungi, bacteria, and insects and correspond to an interesting chemical class ubiquitously found in nature. The [rel-8α-Hydroxy-5-hydroxymethyl-2-methoxy-8α, β-methyl-7, 8, 8a, 9-tetahydro-1, 4-anthracenedione] [oncocalyxone A, onco-A] is a benzoquinone of dark red color isolated from the ethanolic extract of the species Cordia oncocalyx (Auxemma oncocalyx Allem). In this review, we aimed to investigate the main biological activities described for oncocalyxone A, as well as its isolation and characterization processes. For this review, the following descriptors were employed in multiple databases: medicinal plants, quinones, Auxemma oncocalyx, Cordia oncocalyx, biological activity. Besides, experimental papers published in international journals and with full text available were used as inclusion criteria. The biological activity profiles found for onco-A according to the literature were: antiproliferative/cytotoxic effects against SW1573 (alveolar cell carcinoma) and CCD922 (normal skin fibroblasts) cell lines; anti-inflammatory and analgesic potential; inhibitory effect on cell growth and DNA reactivity; antiplatelet activity; antitumor potential; anti-glycation agent; beneficial and/or toxic potential in goats and neuroinhibitory effect; antibacterial and antibiofilm activity. The substance has a broad spectrum of pharmacological applications, most of which are associated with its cytotoxic activity. The work also intends to compile the activities described in the literature, to understand how the molecule acts on the various targets, but, in some cases, more in-depth research is needed to elucidate the mechanisms of action.